Pengaruh Terpaan Iklan Televisi dan Daya Tarik Celebrity Endorser dalam Kampanye #RambutAkuKataAku terhadap Keputusan Pemebelian Shampo Dove - Fidella Nala Sani; Sri Widowati Herieningsih (Interaksi Online, 2021)
Currently, the development of shampoo in Indonesia is increasingly diverse with a large variety of existing shampoos aimed to various groups. The shampoo sales market in Indonesia continues to develop, accompanied by the emergence of various new brands and new innovations. To keep improving and maintaining their shampoo products in the Indonesian market, Dove communicates their shampoo through the "Rambut Aku Kata Aku" campaign using advertisements on television and celebrity endorsers. This study aims to determine the effect of television advertisements exposure and the attractiveness of celebrity endorsers in #RambutAkuKataAku campaign on Dove shampoo buying decisions. The theories used are management function theory, strong advertising theory and cognitive response theory. The sampling technique used nonprobability sampling technique with a sample size of 100 people. Tests are carried out using multiple linear regression analysis and simple linear regression. The results of the study indicate that television advertisements exposure and the attractiveness of celebrity endorsers together have a very significant and positive effect on Dove shampoo buying decisions. Then based on the results of further analysis, television advertisements exposure has a positive effect on buying decisions, as well as attractiveness of celebrity endorser has a positive effect on Dove shampoo buying decisions. With these results, it is suggested to show the advertised products more clearly, not only at the end of the advertisement, and also that celebrity endorsers should explain in detail about the advertised products.